New Concepts in the Teaching and Research of Law - Avendaño Valdez, Jorge (1969)
The article points out the need to reform the way law is taught at the college. The author claims that the teaching assumes a decoupling between law and reality. In this way, the student receives a broad legal and especially theoretical framework, but is not educated to apply this knowledge in reality. This situation has unfavorable consequences for the future lawyers, who will not only find in practice the skills necessary to practice the profession, but also will not be able to verify the effectiveness of the normative requirements. For these reasons, the author proposes to replace the traditional teaching method with a method that takes into account the knowledge taught in legal education and its application to the social reality of the country. In this framework, it is proposed, for example, to teach with the help of teaching materials that have an essential content and aim to solve real cases, as well as with the help of curriculum flexibility aimed at including subjects with multidisciplinary approaches. Finally, it is pointed out that legal research should serve as a tool to consolidate the acquired knowledge and achieve a new vision of law rooted in the reality of the country.